Pain catastrophizing and interpersonal problems: a circumplex analysis of the communal coping model - Lackner, Jeffrey M; Gurtman, Michael B (Pain (Amsterdam), 2004)
Using the circumplex model of interpersonal behavior [Handbook of research methods in clinical psychology, 1982], this study tested the communal coping model of catastrophizing (CCM) in a large (N = 179) sample of patients with irritable bowel syndrome (IBS), a common, benign chronic pain disorder associated with significant painful extraintestinal comorbidity (e.g. headache, low back pain). Patients completed the Coping Strategies Questionnaire, the Brief Symptom Inventory, and the Inventory of Interpersonal Problems. The main findings were: (1) individuals who reported higher levels of catastrophizing described greater interpersonal problems; (2) the interpersonal problems described by catastrophizers fell within the friendly and friendly submissive quadrants of the circumplex supporting the notion that they have an interpersonal style demanding support and care-taking [Pain 103 (2003) 151]; (3) the pain coping behavior most strongly associated with interpersonal problems was catastrophizing; and (4) the relationship between interpersonal problems and catastrophizing remained after removing the influence of general symptomatic distress (i.e. an overall tendency to complain of psychological problems in general). In general, data provide evidence supporting the interpersonal distinctiveness of pain catastrophizing as postulated by the CCM. Advantages of a circumplex model and of interpersonal theory for understanding and testing the CCM are discussed.